EFL Junior High School Students' Perception of Collaborative Writing - Azzura, Della Nur; Al-Baekani, Abdul Kodir; Wachyudi, Kelik (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This research aimed to learn what the students thought about using collaborative techniques in writing a text. A case study was chosen as the research design in this research, with a qualitative approach. Data collection for this research was interviews. The researcher utilized interviews to get a deeper understanding of students' perspectives. To evaluate the data, the researcher applied theories from Miles et al. (2014). Based on the interviews, the researcher concluded that students preferred collaborative writing over writing alone because it was quicker, simpler, and more enjoyable. This was supported by the research's findings. Along with the benefits, students also experienced challenges due to individuality and differences in opinion when writing text through collaborative techniques.